Experimental and Numerical Study of Turbulent Fluid Flow and Heat Transfer of Al2O3/Water Nanofluid in a Spiral-Coil Tube. Issue 6 (13th April 2017) - Doshmanziari, Faramarz Ilami; Kadivar, Mohammad Reza; Yaghoubi, Mahmood; Jalali-Vahid, Davood; Arvinfar, Mohammad Ali
ABSTRACT: Enhancement of heat transfer by nanofluids is reported by a large number of researchers. In this study, numerical and experimental investigation of heat transfer and flow characteristics of Al2 O3 /water nanofluid flowing in a spiral-coil tube is performed for various flow conditions. The spiral-coil tube is immersed horizontally in a hot water bath maintained at 60°C. Experiments are conducted in a turbulent flow regime using distilled water and nanofluid with 0.5%, 1%, and 1.5% particle volume concentrations. Also, a computational fluid dynamics methodology is used to simulate heat transfer and flow characteristics corresponding to the experimental measurements and for further flow conditions. Simulation results are compared with the experimental measurements, and 85% agreement between the results is observed. The results showed that convective heat transfer coefficient of nanofluid is enhanced up to 61% compared with that of the base fluid. Based on the experimental measurements, a new correlation is developed to predict convection heat transfer from nanofluids in spiral-coil tubes.